PENGARUH MODEL PEMBELAJARAN THINK-PAIR- SHARE (TPS) DISERTAI METODE GUIDED NOTE TAKING (GNT) TERHADAP AKTIVITAS DAN HASIL BELAJAR KOGNITIF PADA PEMBELAJARAN FISIKA POKOK BAHASAN GERAK LURUS DI SMA NEGERI RAMBIPUJI - Musa’adatul Rizkiyah; Trapsilo Prihandono; Bambang Supriadi (JURNAL PEMBELAJARAN FISIKA, 2017)
The aimed of this research was to study the influence of think pair share model with guided note taking metode through the activity of student's and the student result in kognitif learning physics. The activity in this case was student activities during the learning process and the learning outcomes in learning physics. This research was experiment research. the research was in SMA Negeri Rambipuji. The data are collected by test, observation, interview, and documentation. to examined the hypothesis, this research used independent sample t-test using SPSS 22 . According to independent sample t-test analysis in the students activity , show that H0 is rejected, it mean that the students activity of experiment class was different with control class. The result of independent sample t-test analysis in the learning outcomes showed that H0 is rejected, it mean that the student result of experiment class was different with control class. and the kognitif learning outcomes learning physics, showed that H0 is rejected, it mean that the student activity of experiment class is different with control class. The conclusion was the think pair share model with guided note taking methode has an significance influential to the activity of student’s and the cognitive learning outcomes SMA Negeri Rambipuji. Key words: Student Result, Activity of Student’s , Cognitive Learning Physics , Guided Note Taking Metode , Think-Pair-Share.